In Vivo Exposure of Deltamethrin Dysregulates the NFAT Signalling Pathway and Induces Lung Damage - Prakriti Sharma; R. S. Sethi (Journal of Toxicology)
Deltamethrin is an insecticide used to control harmful agricultural insects that otherwise damage crops and to control vector-borne diseases. Long-term exposure to deltamethrin results in the inflammation of the lungs. The present study elucidates the molecular mechanism underlying the deltamethrin-induced lung damage. The lung samples were extracted from the Swiss albino mice following the treatment of low (2.5 mg/kg) and high (5 mg/kg) doses of deltamethrin. The mRNA expression of TCR, IL-4, and IL-13 showed upregulation, while the expression of NFAT and FOS was downregulated following a low dose of deltamethrin. Moreover, the expression of TCR was downregulated with the exposure of a high dose of deltamethrin. Furthermore, the immunohistochemistry data confirmed the pattern of protein expression for TCR, FOS, IL-4, and IL-13 following a low dose of deltamethrin exposure. However, no change was seen in the TCR, NFAT, FOS, JUN, IL-4, and IL-13 immunopositive cells of the high-dose treatment group. Also, ELISA results showed increased expression of IL-13 in the BAL fluid of animals exposed to low doses of deltamethrin. Overall, the present study showed that deltamethrin exposure induces lung damage and immune dysregulation via dysregulating the NFAT signalling pathway.